The Brazilian managed prices formation - Campedelli, André Luis (Brazilian Keynesian Review, 2022)
Managed prices correspond to a significant part of the Brazilian inflationary formation, being that they have peculiar characteristics from those which are freely defined. Besides being readjusted via stipulated rules in contracts, its variation happens periodically, and it is often based on past inflation indexes. The purpose of this paper is to analyze how managed prices are formed and observe possible particular features that influence the Brazilian inflation formation. In the first section, managed prices will be defined, whereas in the second section their formation will be observed. In the third section a brief analysis of its peculiarities will be held. The paper is closed with its final considerations.